Emerging Features of Linear Motif-Binding Hub Proteins. Issue 5 (May 2020) - Jespersen, Nathan; Barbar, Elisar
Abstract : Hub proteins are important elements of interactomes within an organism; they bind diverse partners, display significant pleiotropy, and connect many cellular systems. Static hubs interact with their partners simultaneously, while dynamic hubs bind different partners at different locations and times. Although this distinguishes some features of hub protein/partner interactions, the increasing literature requires an expanded categorization of molecular and functional properties. Here, we focus on dynein light chain LC8 as a canonical example of dynamic hub proteins to develop a conceptual residue-level framework for hub–partner interactions and functions. We propose a new class of structural linear motif-binding hub proteins (LMB-hubs) with key common features. LMB-hubs have structural plasticity yet conserved interfaces, can function as integral members of large multimolecular assemblies, and are self-regulating. Highlights: Hub proteins bind multiple diverse partner proteins and connect numerous components of a cellular system. LMB-hubs represent a newly defined class of hubs that target an 8–10-residue consensus motif on a partner protein. LMB-hubs have a highly conserved binding groove that is also remarkably flexible, suggesting that dynamic plasticity underlies its partner binding selectivity and diversity. Structural LMB-hubs stabilize partner–protein complexes that nucleate formation of large molecular assemblies, while enzymatic LMB-hubs transiently interact with consensus motifs. Cellular availability of the LMB-hub LC8 is exquisitely controlled by feedback regulation of transcription factor ASCIZ. Using recently developed motif prediction tools for LMB-hub 14-3-3, we propose autoregulation as a general mechanism for controlling cellular concentrations of LMB-hubs.